ExPEC Acute fibrinonecrotizing pneumonia in a cat - Tondo, Luís Antônio Scalabrin; Cecco, Bianca S. de; Wenzlow, Nanny (Brazilian Journal of Veterinary Pathology, 2024)
A twelve-year-old spayed female cat presented with lethargy and dehydration. Severe pleural effusion was identified during thoracic cavity TFAST ultrasound. Samples of the effusion were submitted for cytology evaluation, and lymphocytic effusion with long-chained rods was diagnosed. The cat stayed hospitalized for 4 days, and despite treatment, the cat died. The other five cats within the same household presented similar clinical signs. The cat was submitted for post-mortem evaluation.